America and the Limits of the Politics of Selfishness - Waldman, Sidney (Lexington Books, 2007)
America and the Limits of the Politics of Selfishness examines Congress, the Presidency, the public, and public policy, demonstrating the important impact of the public's selfishness, morality, compassion, and religious beliefs on the American political system. The influence of public opinion on our democratically elected leaders affects whether our country will be able to find solutions to some of its more important problems. The public's self-love—an exclusive or excessive regard for oneself and one's interests, unbalanced by a concern for others beyond one's family—is critical in impacting the quality of our political system. For example, Waldman illustrates how the public affects the government's ability to solve the problem of failing education in our cities and rural towns. Ultimately, this work reveals the importance of compassion, morality, and religion in dealing with the problem of excessive self-love, with great practical consequences for our country, our own welfare, and that of the world.